Cyclic and Lasso Peptides: Sequence Determination, Topology Analysis, and Rotaxane Formation - Raj, Monika (Angew Chem Int Ed Engl, 2018)
A broadly-applicable chemical cleavage methodology to facilitate MS/MS sequencing was developed for macrocyclic and lasso peptides, which holds promise as exciting new therapeutics. Existing methods such as Edman degradation, CNBr cleavage, and enzymatic digestion are either limited in scope or completely fail in cleavage of constrained non-ribosomal peptides. Importantly, the new method was utilized for synthesizing a unique peptide-based rotaxane (both cycle and thread) from the lasso peptide, benenodin-1 ΔC5.